A general electromagnetic model and vibration control for shape deviations in PMSM supported by three-pole active magnetic bearings. (September 2021) - Xu, Xueping; Han, Qinkai
Highlights: The elliptical and corrugated deviations are quantitatively modeled for the first time. A general electromagnetic excitation model considering the shape deviations is proposed. The stiffness linearization of a three-pole AMB is systematically investigated. The iterative sliding mode control method is adopted for vibration control. Different rotating speeds are concerned and corresponding experiments are conducted. Abstract: Shapes deviations in electrical machines are inevitable due to the mechanical stress and uneven temperature, which leads to electromagnetic-magnetic interactions and unwanted vibrations. A general electromagnetic model for the elliptical and corrugated shape deviations is proposed in this paper for the first time. The air–gap length of a permanent magnet synchronous motor (PMSM) with shape deviations is clearly expressed and the electromagnetic excitations are obtained. The three-pole active magnetic bearing (AMB) with simple structure is adopted to suppress the vibration and integrated into the PMSM system. The mechanism of forces generated by the AMB is revealed. The iterative sliding mode control is applied in the control design. Dynamic responses for different combinations of elliptical deviation and corrugated deviation are obtained, and effects of shape deviations in PMSM on vibration characteristics are demonstrated. Excellent performances of the control method for different shape deviation degrees and rotating speeds are achieved and compared. Experiments of a PMSM with elliptical deviations are conducted and vibration control behaviors are analyzed. Results indicate that the existence of shape deviations will increase the vibration displacement. Moreover, the elliptical shape deviation will break the symmetry of the rotor orbit, while the symmetry can be maintained for the corrugated shape deviation. The three-pole AMB together with iterative sliding mode control can be applied for the vibration control of a shape defective PMSM for different rotating speeds. The proposed model for shape deviations and idea of vibration control can improve the insight into dynamic characteristics of electrical machines.